Peran Pendidikan Agama Islam dalam Pengembangan Karakter Jujur Peserta Didik - Hidayat Hidayat (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study was conducted to measure the attitude of honesty in each student in grade V of SDI al Rasyid Elementary School Pekanbaru. The method used in this study is a descriptive method with a quantitative approach. The sample in this study were grade V students at SDI al Rasyid Pekanbaru. The data collection technique used observation, this was done by researchers by directly reviewing the field as a research object to obtain data, then the researcher gave a questionnaire. From the results of the data obtained, the average number of honesty attitudes of students in grade V was 80.23, a fairly large number which means that it provides a conclusion that the honest attitudes possessed by students are quite good and high. This is inseparable from the role of education that always shapes and directs them in everyday life, the role of education both in schools, families and the community environment is a supporting factor in character building or honest attitudes towards students.